Next-generation vascular organoids: multi-lineage and immune integration for disease modeling and regenerative medicine - Qiaowen Chen; Jiale Jin; Fahsai Kantawong; Guang Li; Jingyan Li (Vessel Plus, 2026)
Traditional human blood vessel organoids, built primarily around endothelial monocultures, fail to replicate the multicellular architecture and dynamic immunological functions of native microvasculature. This review synthesizes an emerging paradigm shift toward third-generation, multi-lineage, and immune-competent vascular organoids. Multicellular integration, combining perivascular mural lineages (pericytes and vascular smooth muscle cells) with functional immune populations (macrophages, microglia, and lymphocytes), is delineated. Its role in reinstating baseline barrier tightness, contractility, and tissue-level immunosurveillance is highlighted. Critical bioengineering workflows are examined, with emphasis on fluidic shear stress in microfluidic platforms, the spatial precision afforded by three-dimensional (3D) bioprinting, and multiplex CRISPR gene editing. These technologies resolve lineage-specific media conflicts and enable off-the-shelf, hypoimmunogenic vascular constructs. Furthermore, the capacity of these systems to recapitulate complex pathophysiology is evaluated. Such pathophysiology includes complement-driven immunothrombosis in SARS-CoV-2 infection, neurovascular degeneration in Alzheimer’s disease, genetic small-vessel disorders, and tumor-immune barriers that govern chimeric antigen receptor T (CAR-T) cell infiltration. Finally, persistent translational hurdles are outlined, including metabolic bottlenecks, diffusion limits, scale‑up challenges, and the lack of large‑animal efficacy and safety data. Strategies that may help transition these models from research tools toward clinically relevant platforms are also discussed.